Czy ludzkość „poprawiona naukowo” może być wolna? Dystopie Aldousa Huxleya, Stanisława Lema i Anthony’ego Burgessa w świetle myśli Ericha Fromma - Oramus, Dominika (Civitas. Studia z filozofii polityki, 2011)
The author refers to three authors, Anthony Burgess, Aldous Huxley and Stanisław Lem, who, when building their visions of a biologically ‘amended’ society, imbue them with their apprehensions of the psychological consequences of civilisation’s further development; the more or less voluntary limitation of the freedom of the individual, globalisation, the domination of ‘dumbed-down’ popular culture and advanced science and technology at the service of the ruling elite. The writers and the philosopher continually warned the reader that a combination of these factors will result in the emergence of a new totalitarianism, a dictatorship disguised as an apparently permissive utopia. The author demonstrates how the writers in question are part of the pessimistic stream of reflection on humankind which dominated the Western thought of the mid-20th century and which found its fullest reflection in Erich Fromm’s Escape from Freedom.